Experiment study on chloride corrosion deterioration of load-bearing concrete segment. Issue 4 (March 2019) - Feng, Kun; Liu, Sijin; He, Chuan; Peng, Zuzhao; Gou, Chao; Zhang, Haihua; Sun, Qi
In order to study the combined action of compression-bending load and surrounding ion erosive environment on underwater shield tunnel, a series of cofferdam-type electrochemical-accelerated corrosion tests of mini segments are carried out to investigate the segment reinforcement corrosion under different compression-bending loads and the change of internal force and rigidity of mini segments under different load-bearing and corroding conditions. Then, the failure pattern of mini segments under different loading and corroding states are recorded and analyzed. The results indicate that the following: (1) the larger the external load, the shorter the initial rust time of the steel bar; (2) the corrosion rate of steel bar increases linearly with time, and the ratio of corrosion of steel bar increases quadratically with time, the larger the load, the more obvious the increase will be; (3) after the corrosion of steel bar, the change rate of the strain for the steel bar increases as the external load augments, and as a matter of fact, the change rate of the strain increases as well, besides, the degree of strain change for compressive steel is obviously lower compared with that of tensile steel bar; (4) the effect of electric corrosion on the deflection of the segments is more obvious with the increase of external load, and a quadratic increase relationship between the deflection and the corrosion is observed in the process of corrosion; (5) It can be concluded that plastic failure is observed for the segments without loading and for those without cracks in the initial stage of loading, which can be indicated directly by the relatively smaller loss rate of steel section, while brittle failure is presented as the failure pattern for the segments with cracks after loading for certain period, which means the loss rate of steel section is relatively larger. The results can briefly provide useful reference for rational design and durability assessment of shield tunnel segmental linings.